PENGANTAR ILMU HADIS DAN CABANG-CABANG ILMU HADIS - Herin Supardi (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2022)
Etymologically the word "science of hadith" is an absorption word from Arabic, "Ilmu al-hadith" which consists of two words, namely "science" and "hadith". If it refers to the meaning of hadith, it means that science studies or discusses everything that is based on the Prophet SAW, whether in the form of words, deeds, takrir or others. If you look at the outline, it is divided into two parts. First, the Science of Hadith History (riwayah) second, Imu Hadith Dirayat (dirayah).